Downregulation of Wip1 phosphatase modulates the cellular threshold of DNA damage signaling in mitosis - Macurek, Libor; Benada, Jan; Müllers, Erik; Halim, Vincentius A; Krejčíková, Kateřina; Burdová, Kamila; Pecháčková, Sona; Hodný, Zdeněk; Lindqvist, Arne; Medema, René H; Bartek, Jiri (Cell cycle (Georgetown, Tex.), 2013)
Cells are constantly challenged by DNA damage and protect their genome integrity by activation of an evolutionary conserved DNA damage response pathway (DDR). A central core of DDR is composed of a spatiotemporally ordered net of post-translational modifications, among which protein phosphorylation plays a major role. Activation of checkpoint kinases ATM/ATR and Chk1/2 leads to a temporal arrest in cell cycle progression (checkpoint) and allows time for DNA repair. Following DNA repair, cells re-enter the cell cycle by checkpoint recovery. Wip1 phosphatase (also called PPM1D) dephosphorylates multiple proteins involved in DDR and is essential for timely termination of the DDR. Here we have investigated how Wip1 is regulated in the context of the cell cycle. We found that Wip1 activity is downregulated by several mechanisms during mitosis. Wip1 protein abundance increases from G(1) phase to G(2) and declines in mitosis. Decreased abundance of Wip1 during mitosis is caused by proteasomal degradation. In addition, Wip1 is phosphorylated at multiple residues during mitosis, and this leads to inhibition of its enzymatic activity. Importantly, ectopic expression of Wip1 reduced γH2AX staining in mitotic cells and decreased the number of 53BP1 nuclear bodies in G(1) cells. We propose that the combined decrease and inhibition of Wip1 in mitosis decreases the threshold necessary for DDR activation and enables cells to react adequately even to modest levels of DNA damage encountered during unperturbed mitotic progression.
Keywords: Gene Expression Regulation; transfekce; poškození DNA; γH2AX; kvantitativní polymerázová řetězová reakce; DNA Damage; Cell Line, Tumor; Phosphoprotein Phosphatases; Fluorescent Antibody Technique; fluorescenční protilátková technika; Transfection; fosforylace; signální transdukce; Phosphorylation; Mitosis; M Phase Cell Cycle Checkpoints; DNA Primers; Mass Spectrometry; Real-Time Polymerase Chain Reaction; Wip1 phosphatase; cell cycle; proteinfosfatasy; Signal Transduction; RNA, Small Interfering; lidé; Humans; malá interferující RNA; regulace genové exprese; Protein Phosphatase 2C; kontrolní body M fáze buněčného cyklu; DNA primery; mitotic progression; hmotnostní spektrometrie; mitóza; proteinfosfatasa 2C; nádorové buněčné linie; DNA damage response